Functional recovery of stored platelets after transfusion. Issue 5 (2nd March 2016) - Bikker, Angela; Bouman, Esther; Sebastian, Silvie; Korporaal, Suzanne J.A.; Urbanus, Rolf T.; Fijnheer, Rob; Boven, Leonie A.; Roest, Mark
Abstract : BACKGROUND: Platelet (PLT) concentrates are prophylactically given to prevent major bleeding complications. The corrected count increment (CCI) is currently the only tool to monitor PLT transfusion efficacy. PLT function tests cannot be performed in patients with thrombocytopenia. Therefore, an optimized agonist‐induced assay was used to determine PLT function, in patients with severe thrombocytopenia before and after transfusion. STUDY DESIGN AND METHODS: PLT reactivity toward adenosine diphosphate (ADP), thrombin receptor–activating peptide SFLLRN (TRAP), and convulxin (CVX) was assessed by flow cytometry. P‐selectin expression was measured on PLTs from 11 patients with thrombocytopenia before and 1 hour after transfusion, on stored PLTs, and on stored PLTs incubated for 1 hour in whole blood from patients ex vivo. RESULTS: The mean (±SEM) CCI after 1 hour was 11.4 (±1.5). After transfusion, maximal agonist‐induced PLT P‐selectin expression was on average 29% higher for ADP (p = 0.02), 25% higher for TRAP (p = 0.007), and 24% higher for CVX (p = 0.0008). ADP‐induced reactivity of stored PLTs increased with 46% after ex vivo incubation (p = 0.007). These PLTs also showed an overall higher P‐selectin expression compared to PLTs 1 hour after transfusion (p = 0.005). After normalization for this background expression, a similar responsiveness was observed. CONCLUSIONS: Our study shows recovery of PLT function after transfusion in patients with thrombocytopenia. The majority of functional PLTs measured after transfusion most likely represents stored transfused PLTs that regained functionality in vivo. The difference in baseline P‐selectin expression in vivo versus ex vivo suggests a rapid clearance from circulation of PLTs with increased P‐selectin expression.